Magnetic field–induced type II Weyl semimetallic state in geometrically frustrated Shastry-Sutherland lattice GdB4. (December 2019) - Shon, W.; Ryu, D.-C.; Kim, K.; Min, B.I.; Kim, B.; Kang, B.; Cho, B.K.; Kim, H.-J.; Rhyee, J.-S.
Abstract: Weyl semimetal is a topologically non-trivial phase of matter with pairs of Weyl nodes in the k-space, which act as monopole and antimonopole pairs of the Berry curvature. Two hallmarks of the Weyl metallic state are the topological surface state called the Fermi arc and the chiral anomaly. It is known that the chiral anomaly yields anomalous magnetotransport phenomena. In this study, we report the emergence of the type II Weyl semimetallic state in the geometrically frustrated non-collinear antiferromagnetic Shastry-Sutherland lattice (SSL) GdB4 crystal. When we apply magnetic fields perpendicular to the non-collinear moments in the SSL plane, Weyl nodes are created above and below the Fermi energy along the M-A line (τ-band) because the spin tilting breaks the time-reversal symmetry and lifts band degeneracy while preserving C 4 z or C 2 z symmetry. The unique electronic structure of GdB4 under magnetic fields applied perpendicular to the SSL gives rise to a non-trivial Berry phase, detected in de Haas-van Alphen experiments, and chiral anomaly–induced negative magnetoresistance. The emergence of the magnetic field–induced Weyl state in the SSL presents a new guiding principle to develop novel types of Weyl semimetals in frustrated spin systems. Graphical abstract: (a–d) Fermi surfaces of GdB4 . For clarity, we separated each Fermi surface. Integrated Berry curvature near the M-point ( τ and δ orbits) (e) and Z-point ( α orbit) (f). (g) Weyl points of W1, W2, and W3 (the same band points in Fig. 3(d)) along the Γ-Z line. Image 1 Highlights: We present a new type of magnetic field–induced type II Weyl semimetallic state in the geometrically frustrated Shastry-Sutherland lattice (SSL). Non-trivial Berry phase is observed from de Haas-van Alphen experiment of the GdB4 single crystal. We identify magnetic field–induced Weyl nodes and spin chirality from band structure calculation of GdB4 . We observe a chiral anomaly and anomalous magnetoconductivity when the direction of a magnetic field is parallel with those of an electric field. We demonstrate a topological phase evolution in terms of magnetic field strength in the SSL.